1998
DOI: 10.1080/07366299808934533
|View full text |Cite
|
Sign up to set email alerts
|

Surface Impregnated Sulfonate Ion Exchangers: Preparation, Properties and Application

Abstract: This paper reviews the results obtained by studying Surface Impregnated Sulfonate Ion Exchangers (SISIE) obtained by modification of macroporous or gel polysterene-divinylbenzene polymers with toluene solutions of dinonylnaphthalene sulfonic acids. Capacities of SISIE of the first type are directly proportional to the concentration of the modifying solution and to the specific surface area of the matrix. Capacities of gel SISIE are much less than those of macroporous samples and depend on the crosslinking of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…The impregnating extractant located in the pore volume is weakly retained by the polymer (mainly due to the capillary forces) and can be easily leached out from the freshly prepared EIR samples during the first days of its use (unstable part of EIR capacity). The impregnating extractant taken up by the gel regions of the matrix represents the most stable part of the EIR capacity, which remains practically constant for a long period [39,40]. Thus, for stabilizing the EIR capacity (the amount of extractant impregnated on the resin) 15 cycles of sorption-desorption were carried out by treating the EIR samples with 100-mL aliquots of Hg(VI) solution having high concentration (500 mg L −1 at the optimum pH and ionic strengths) and 10-mL aliquots of HCl 4 M solution as eluent.…”
Section: Preparation and Characterization Of Tan-impregnated Resinmentioning
confidence: 99%
“…The impregnating extractant located in the pore volume is weakly retained by the polymer (mainly due to the capillary forces) and can be easily leached out from the freshly prepared EIR samples during the first days of its use (unstable part of EIR capacity). The impregnating extractant taken up by the gel regions of the matrix represents the most stable part of the EIR capacity, which remains practically constant for a long period [39,40]. Thus, for stabilizing the EIR capacity (the amount of extractant impregnated on the resin) 15 cycles of sorption-desorption were carried out by treating the EIR samples with 100-mL aliquots of Hg(VI) solution having high concentration (500 mg L −1 at the optimum pH and ionic strengths) and 10-mL aliquots of HCl 4 M solution as eluent.…”
Section: Preparation and Characterization Of Tan-impregnated Resinmentioning
confidence: 99%
“…Muraviev [53] intensively discussed the wet drying technique and revealed that the IX interaction on SIRs proceeds faster after the wet drying procedure and it can improve the kinetic characteristics of SIRs. However, this method disposes a certain amount of extractant weakly retained by the polymer and inevitably reduces the absorption capacity.…”
Section: Preparation Of High-stability Sirsmentioning
confidence: 99%
“…These values are in accordance with the specific surface area sequence of prepared materials since their values are 466.76, 322.49 and 6.91 m 2 /g. Muraviev [24] in 1998 mentioned that the capacity of solvent impregnated resins depends on the concentration of extractant in the impregnating (organic) solution, the swelling of the polymer beads in this solution and the porosity of the polymer. In this study, the first parameter is excluded as the concentration of combined solvents is fixed with respect to the three bases, the other parameters are effective in the preparation of the three resins.…”
Section: Sorption Capacitymentioning
confidence: 99%
“…In this study, the first parameter is excluded as the concentration of combined solvents is fixed with respect to the three bases, the other parameters are effective in the preparation of the three resins. In this concern, many researches have mentioned that Amberlite XAD4 [24] and silica gel [25] have high swelling in the organic solvents while the swelling of wood is slight due to the hydrogen bonding properties of organic liquids [26]. The porosity of the polymer is another parameter which strongly influences the capacity of the resins [27] since the high porosity of the polymeric support leads to higher volumetric uptake of the organic solvents.…”
Section: Sorption Capacitymentioning
confidence: 99%